(untitled) (Proceedings of International Conference on Special Education, 2025)
Students with Special Educational Needs (SEN) also referred to locally in Malaysia as MBPK (Murid Berkeperluan Pendidikan Khas) are students requiring educational adaptations due to learning difficulties, disabilities or other developmental needs. Parents’ understanding and awareness of the future potential of SEN students remain limited, often constrained by traditional beliefs that their children do not have the same promising future as typical students. This study aims to evaluate the effectiveness of a networking and collaboration program designed to enhance parents’ awareness and understanding of the educational and career pathways available to SEN students secondary school graduates in the Kuala Langat district, Selangor. This study employed a quantitative survey approach, supported by qualitative feedback to enrich and contextualize the findings. A career fair and networking event was carried out involving private and governmental agencies as well as education providers. This program was attended by SEN students and their parents. A total of 56 respondents were selected to answer the survey questionnaire at the end of the program. The findings indicate that this program has succeeded in increasing parents’ understanding of educational opportunities such as skills certificate programs, as well as industry-to-career training which directly increases parents’ confidence in guiding SEN students towards an educational path that is more suitable for their children’s interests and abilities after graduating from school. Overall, this study is important in providing a platform for collaboration between schools, parents and post-secondary institutions in helping to shape a more secure direction for their future. This study also suggests the need for more comprehensive programs like these to be held across the nation. The findings may assist policymakers and education practitioners in developing a holistic approach to address the issue as well as improving the special education support system in Malaysia.